Ambulatory blood pressure variability increases over a 19-year follow-up in a clinic on a solitary island. Issue 6 (December 2018) - Narita, Keisuke; Eguchi, Kazuo; Kario, Kazuomi
Abstract : Objective: This study investigated the changes of ambulatory blood pressure (ABP) profiles on the same participants over a 19-year follow-up. Participants and methods: This is a longitudinal study. We conducted 24-h ABP monitoring at baseline in November 1997 and at follow-up in November 2016 for the same participants who were outpatients in a solitary island clinic. To estimate ambulatory blood pressure variability (ABPV), SD, coefficient of variation, and average real variability of ABP were calculated. ABP levels and ABPV at baseline and follow-up were compared using paired t -test. Results: A total of 35 participants were recruited at follow-up (79.3±6.7 years at follow-up). Mean systolic blood pressure levels in 24-h, daytime, and night-time did not change significantly. However, ABPV of systolic/diastolic blood pressure in 24-h and daytime increased at follow-up compared with baseline ( P <0.01 in all variables: SD, coefficient of variation, and average real variability), whereas ABPV in night-time did not change significantly. Conclusion: Our observations suggested that 24-h and daytime ABPV increase with aging in community-dwelling elderly people. Abstract : Supplemental Digital Content is available in the text.